Pleomorphic adenoma of the upper lip: a case report and review of literature - Metgud, Rashmi; Neelesh, Bhardwaj Tina; Goel, Saurabh; Nail, Smitha; Patel, Shrikant; Tak, Anirrudh (International Journal of Dental Research, 2016)
Pleomorphic Adenoma is a benign epithelial tumor arising from the salivary gland. It is a benign mixed tumor composed of epithelial and myoepithelial cells arranged with various morphological patterns, demarcated from surrounding tissues by fibrous capsule. In this article, we report an unusual case of 30 year, male with a single, nodular swelling evident in the upper lip which was discovered during a routine dental procedure. Fine Needle Aspiration Cytology (FNAC) was planned for the patient, where a of cytological diagnosis of Pleomorphic Adenoma was rendered, which was confirmed by biopsy. Hence, this highlights, FNAC makes up an important diagnosing tool as the first line of investigation to distinguish between benign and malignant salivary gland neoplasms.